Causation and Laws of Nature
XVI, 359 p.
Keywords: Causation and Laws of Nature is a collection of articles which represents current research on the metaphysics of causation and laws of nature, mostly by authors working in or active in the Australasian region. The book provides an overview of current work on the theory of causation, including counterfactual, singularist, nomological and causal process approaches. It also covers work on the nature of laws of nature, with special emphasis on the scientific essentialist theory that laws of nature are, at base, the fundamental dispositions or capacities of natural kinds of things. Because the book represents a good cross-section of authors currently working on these themes in the Australasian region, it conveys something of the interest and excitement of an active philosophical debate between advocates of several different research programmes in the area.